Endogenous Production of Hydrogen Sulfide in Human Sinus Mucosa and its Expression Levels are Altered in Patients with Chronic Rhinosinusitis with and without Nasal Polyps. Issue 1 (January 2014) - Hwang, Jae Woong; Jun, Young Joon; Park, Se Jin; Kim, Tae Hoon; Lee, Ki Jeong; Hwang, Soo Min; Lee, Seung Hoon; Lee, Heung Man; Lee, Sang Hag
Background: Chronic rhinosinusitis with nasal polyps (CRSwNPs) or CRS without nasal polyps (CRSsNPs) is characterized by persistent inflammation of sinonasal mucosa. No one causative factor fully explains for the pathological manifestations of CRS. Endogenous hydrogen sulfide (H2 S) has been shown to participate in inflammatory diseases, functioning as an inflammatory mediator in various organs. We analyzed the contents and synthesis activity of H2 S, the expression and distribution pattern of H2 S-generating enzymes, cystathione β-synthase (CBS), and cystathione γ-lyase (CSE) in CRSwNPs and CRSsNPs. The effects of H2 S on the expression of CRS-relevant cytokines and the effects of cytokines on the expression of CBS and CSE were assessed in an in vitro experiment. Methods: The contents and synthesis activity of H2 S and the expression and distribution pattern of CBS and CSE in sinus mucosa were evaluated using spectrophotometry, real-time polymerase chain reaction, Western blot, and immunohistochemistry. Cultured epithelial cells were used to elucidate the effects of H2 S donor, sodium hydrosulfide (NaHS), on the expression of CRS-relevant cytokines and the effects of cytokines on H2 S-generating enzymes expression. Results: The contents and synthesis activity of H2 S were increased in CRSwNPs and CRSsNPs. CBS and CSE were localized to the superficial epithelium and submucosal glands, but CSE was also found in vascular endothelium. N S induced increased expression of IL-4, IL-5, interferon γ, and TNF-α. CBS and CSE expression in cultured cells was up-regulated by CRS-relevant cytokines. Conclusion: H2 S levels are increased in CRS, contributing to increased production of cytokines. These results suggest that H2 S may function as inflammatory mediator in CRS.